ADJECTIVES IN TAMIL AND URDU – A COMPARATIVE STUDY - Ali, Mubarak (International Journal of Research -GRANTHAALAYAH, 2016)
The aim of the paper is to compare the adjectives of Tamil Language which is one of the languages of Dravidian family and Urdu which is one of the members of Indo-Aryan family and bring out similarities and differences in their formation and usage in these two languages.